Post-Thaw Characteristics of the Simmental Sperm Function in Different Ages of Bulls - F. A. Satrio; N. W. K. Karja; M. A. Setiadi; E. M. Kaiin; M. Gunawan; B. Purwantara (Tropical Animal Science Journal, 2022)
This study aims to determine the effect of the age difference of Simmental bulls on motion characteristics, capacitation status, and DNA fragmentation of post-thawing sperms. The frozen semen used was collected from twelve bulls, which were divided into four groups of age, which include a group of two, four, ≥ 10 years old with high semen rejection (≥ 10 HR), and ≥ 10 years old with low semen rejection (≥ 10 LR). Computer Assisted Sperm Analysis (CASA) was used to determine sperm motion characteristics, capacitation status by chlortetracycline (CTC) staining, plasma membrane integrity, and viability using eosin-nigrosine staining. In contrast, the DNA fragmentation index was determined using the Sperm-Bos-halomax kit. The results showed that the four year old group had a higher total and progressive motility percentage than the others (p<0.05). In all groups, there was no significant difference among sperm kinematics such as VAP, VSL, VCL, STR, and ALH. However, the LIN, WOB, and BCF of the ≥ 10 HR year old groups were significantly lower (p<0.05) than those of the other groups. However, un-capacitated sperm was higher (p<0.05) in the two years and four years old groups compared to the ≥ 10 years old, while the four years old group had lower capacitated and acrosome-reacted (p<0.05) than the other groups. Furthermore, the sperm membrane integrity, viability, and DNA fragmentation index of the ≥ 10 years old groups were significantly higher (p<0.05) than those of the other groups. The research concludes that aging in the Simmental bull affects motion characteristics, capacitation status, and DNA fragmentation of post-thawing sperm. However, the semen rejection rate in the older bull did not directly affect the post-thawing sperm quality.